Diclofenac derivatives as concomitant inhibitors of cholinesterase, monoamine oxidase, cyclooxygenase-2 and 5-lipoxygenase for the treatment of Alzheimer's disease: synthesis, pharmacology, toxicity and docking studies. Issue 35 (11th August 2022) - Javed, Muhammad Aamir; Bibi, Saba; Jan, Muhammad Saeed; Ikram, Muhammad; Zaidi, Asma; Farooq, Umar; Sadiq, Abdul; Rashid, Umer
Abstract : Targeting concomitantly cholinesterase (ChEs) and monoamine oxidases (MAO-A and MAO-B) is one of the key strategies to treat multifactorial Alzheimer's disease (AD). Abstract : Targeting concomitantly cholinesterase (ChEs) and monoamine oxidases (MAO-A and MAO-B) is a key strategy to treat multifactorial Alzheimer's disease (AD). Moreover, it is reported that the expression of cyclooxygenase-2 (COX-2) and lipoxygenase (LOX) is increased significantly in the brain of AD patients. Using the triazole of diclofenac 12 as a lead compound, we synthesized a variety of analogs as multipotent inhibitors concomitantly targeting COX-2, 5-LOX, AChE, BChE, MAO-A and MAO-B. A number of compounds showed excellent in vitro inhibition of the target biological macromolecules in nanomolar concentration. Compound 39 emerged as the most potent multitarget ligand with IC50 values of 0.03 μM, 0.91 μM, 0.61 μM, 0.01 μM 0.60 μM and 0.98 μM towards AChE, BChE, MAO-A, MAO-B, COX-2 and 5-LOX respectively. All the biologically active compounds were found to be non-neurotoxic and blood–brain barrier penetrant by using PAMPA assay. In a reversibility assay, all the studied active compounds showed reversibility and thus were found to be devoid of side effects. MTT assay results on neuroblastoma SH-SY5Y cells showed that the tested compounds were non-neurotoxic. An in vivo acute toxicity study showed the safety of the synthesized compounds up to a 2000 mg kg −1 dose. In docking studies three-dimensional construction and interaction with key residues of all the studied biological macromolecules helped us to explain the experimental results.